Numerical modeling of laterally loaded piles - Kok, Sien Ti; Kim Huat, Bujang (Science Publications, 2008)
Design of laterally loaded piles due to soil movement relies on a number of theoretical and numerical approaches. However, the magnitude of soil movement is difficult to estimate with reasonable confidence and accuracy. Finite Element Analysis (FEA) offers an excellent alternative to study pile-soil interaction and pile’s response under lateral loading due to soil movement. This research presents published analytical results and case history modeled in a 2D finite element environment in the case of single pile under a non-linear plain strain condition. Reasonable agreement has been achieved in comparing the single pile’s response against published results of the pile near excavation and in sliding slope.